If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 48x + 7x = 12(x + 4) Combine like terms: 5x + 48x = 53x 53x + 7x = 12(x + 4) Combine like terms: 53x + 7x = 60x 60x = 12(x + 4) Reorder the terms: 60x = 12(4 + x) 60x = (4 * 12 + x * 12) 60x = (48 + 12x) Solving 60x = 48 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 60x + -12x = 48 + 12x + -12x Combine like terms: 60x + -12x = 48x 48x = 48 + 12x + -12x Combine like terms: 12x + -12x = 0 48x = 48 + 0 48x = 48 Divide each side by '48'. x = 1 Simplifying x = 1
| 3x+12=3x+15 | | w=190-1900t | | 4(x+3)-x+9= | | 14x+(-13)=-11-4 | | lx-7l=9 | | r-45=27 | | 2+3=81 | | .25x+9=.75x+2 | | 7x+5=8x+5 | | 9(z+3)=8(z-7)+z | | 3x+27=708 | | 5(3x-9)=12 | | p=5X26/1 | | -2(6x-3)=12x+6 | | 2.88=×/.2-× | | z^8/z^17 | | 7m+15=5m+12 | | x+4x-57=43 | | x*x+3x=180 | | 19=-2(4+z) | | y=-33x+4 | | -2(6x-3)=-12x+5 | | 8x/11=48 | | 4-9=4 | | y=-33+4 | | -14+z=26 | | U=1.2u+1.884 | | 12n-5=-2 | | Y=0.45x+32 | | -2(6x-3)=12x-6 | | 4.8m+3.77=-40.87 | | 8(z+10)+x=98 |